Sistem Pemetaan Objek Wisata Berbasis WebGIS di Kabupaten Rote Ndao - Mooy, Denny (STIKOM Uyelindo Kupang, 2022)
Rote Ndao Regency is geographically designated as an autonomous region that has natural and cultural charms. Various types of tourism potential such as natural tourism, spiritual tourism, cultural tourism, culinary tourism, and marine tourism can be found in Rote Ndao Regency. This potential is a very valuable asset in attracting foreign and domestic tourists who visit and enjoy tourism in Rote Ndao Regency. The Ministry of Culture and Tourism of Rote Ndao Regency already has a tourism website, but the absence of several features on the tourism website makes tourists not aware of tourist attractions in the Rote Ndao Government. For that we need a system that is able to provide an overview of tourist destinations. So that later it can help tourists in choosing tourist objects that are suitable for tourists. The Tourism Object Mapping System is based on WebGIS and uses the PHP and MYSQL programming languages ??as databases. The results of this study are in the form of an application that can provide information about a map of the location of tourist attractions, facilities available at tourist attractions, and the distance to tourist attractions in Rote Ndao Regency.